A Hybrid Key Pre-Distribution Scheme for Securing Communications in Wireless Sensor Networks - Mojtaba Jamshidi; Hamid Bazargan; Abdusalam Abdulla Shaltooki; Aso Mohammad Darwesh (JOIV : International Journal on Informatics Visualization, 2019)
Wireless Sensor Network (WSN) is a type of ad hoc networks which consist of hundreds to thousands of sensor nodes. These sensor nodes collaborate to surveillance environment. WSNs have a variety of applications in military, industrial and other fields and they are fit to study environments that presence of human being is costly or dangerous. Sensor nodes have memory, energy and processing limitations. According to sensors' limitations and also increasing use of these networks in military fields, establishing a secure WSN is very important and challenging. Applying Key Predistribution Schemes (KPSs) is one of the effective and useful mechanisms to provide security in WSN. In this paper, a hybrid KPS is proposed that support three various keys, primary pairwise, polynomial, and ordinary. The proposed scheme has been implemented using J-SIM simulator and its performance has been evaluated in terms of maximum supportable network sizes and resiliency against node capture attack, by performing some experiments. Simulation results have been compared with Basic, q-Composite, RS, Cluster-Based, QS, and Double-Key Hash schemes. The compared results showed that the proposed scheme has a better resiliency against links disclosing via enemies.